Intravenous Lidocaine for Rib Fractures: Effect on Pain Control and Outcome. Issue 4 (April 2022) - King, Sarah; Smith, Lou; Harper, Christopher; Beam, Zachary; Heidel, Eric; Carico, Genevieve; Wahler, Kelsey; Daley, Brian
Background: Multimodal analgesia in rib fractures (RFs) is designed to maximize pain control while minimizing narcotics. Prior research with intravenous lidocaine (IVL) efficacy produced conflicting results. We hypothesized IVL infusion reduces opioid utilization and pain scores. Methods: A retrospective review of RF patients at an ACS-verified Level I trauma center from April 2018 to 2/2020 was conducted. Patients (pts) stratified as receiving IVL vs no IVL. Initial lidocaine dose: 1 mg/kg/hr with a maximum of 3 mg/kg/hr. Duration of infusion: 48 h. Pain quantified by the Stanford Pain Score system (PS). Bivariate and multivariate analyses of variables were performed on SPSS, version 21 (IBM Corp). Results: 414 pts met inclusion criteria: 254 males and 160 females. The average age for the non-IVL = 67.4 ± 15.2 years vs IVL = 58.3 ± 17.1 years ( P < .001). There were no statistically significant differences between groups for ISS, PS for initial 48 h, and ICU length of stay (LOS). There was a difference in morphine equivalents per hour: non-IVL = 1.25 vs IVL = 1.72 ( P = .004) and LOS non-IVL = 10.2+/−7.6 vs IVL = 7.82+/−4.94. By analyzing IVL pts in a crossover comparison before and after IVL, there was reduction in opiates: 3.01 vs 1.72 ( P < .001) and PS: 7.0 vs 4.9 ( P < .001). Stanford Pain Score system reduction in the IVL = 48.3 ± 23.9%, but less effective in narcotic dependency (27 ± 22.9%, P = .035); IVL pts had hospital cost reduction: $82, 927 vs $118, 202 ( P < .01). Discussion: In a crossover analysis, IVL is effective for reduction of PS and opiate use and reduces hospital LOS and costs. Patient age may confound interpretation of results. Our data support IVL use in multimodal pain regimens. Future prospective study is warranted.